2006
DOI: 10.1590/s0103-97332006000300042
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the plasmon-LO phonon interaction on the critical densities of RPA approach in a quasi-one-dimensional system

Abstract: In this work we have studied the electron LO phonon interaction on the pair-correlation function g(x) and its dependence on the electronic density for a GaAs-AlGaAs rectangular quantum wire within the random-phase approximation (RPA). We assumed two different values of the wire width. As negative non-physical results are found for lower electronic densities and small interparticle separations in the RPA approach, we have delimited the regions where the RPA approach cannot be used for the calculation of the Q1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In that work, a comparison between the results for S 0 (q x ) calculated within the RPA approach and within the STLS theory, for a GaAs QWW is presented and the authors showed that the inclusion of the LFC effect beyond RPA does not change qualitatively the shape of the structurefactor dispersion relation, but only the values of S 0 (q x ). Also, in the region of small values of q x , S 0 (q x ) increases significantly, indicating that the electron-electron interaction become more effective in this region of short wavevector, a critical region where the RPA approach gives no good results [23].…”
mentioning
confidence: 99%
“…In that work, a comparison between the results for S 0 (q x ) calculated within the RPA approach and within the STLS theory, for a GaAs QWW is presented and the authors showed that the inclusion of the LFC effect beyond RPA does not change qualitatively the shape of the structurefactor dispersion relation, but only the values of S 0 (q x ). Also, in the region of small values of q x , S 0 (q x ) increases significantly, indicating that the electron-electron interaction become more effective in this region of short wavevector, a critical region where the RPA approach gives no good results [23].…”
mentioning
confidence: 99%
“…Under this condition, no contribution of linear momentum by surface modes of lattice vibration in the gold film is required to meet phase matching condition. Therefore, the highest DOC between a pair of SPWs is anticipated due to no random phase disturbance from longitudinal optical phonons in the gold film. , However, the phase matching condition is required too when the incident angle is at an angle small deviated from the on resonance angle to excite SPW in SPR device. Hence, the longitudinal optical phonons are involved to contribute extra-linear momentum to satisfy phase-matching condition for exciting SPW properly. Therefore, in DOC-PSPWB, each SPW excitation requests a different group of longitudinal optical phonons independently to meet the phase-matching condition under the arrangement at a small incident angle deviated from SPW resonance angle.…”
Section: Working Principle Of Doc-pspwbmentioning
confidence: 99%
“…Therefore, the highest DOC between a pair of SPWs is anticipated due to no random phase disturbance from longitudinal optical phonons in the gold film. , However, the phase matching condition is required too when the incident angle is at an angle small deviated from the on resonance angle to excite SPW in SPR device. Hence, the longitudinal optical phonons are involved to contribute extra-linear momentum to satisfy phase-matching condition for exciting SPW properly. Therefore, in DOC-PSPWB, each SPW excitation requests a different group of longitudinal optical phonons independently to meet the phase-matching condition under the arrangement at a small incident angle deviated from SPW resonance angle. As a result, the dephasing (or decorrelated) between paired SPWs becomes sensitive to the distribution of the number of densities of the longitudinal optical phonons in gold film at room temperature.…”
Section: Working Principle Of Doc-pspwbmentioning
confidence: 99%
See 1 more Smart Citation